2015
DOI: 10.1007/978-3-319-27659-5_16
|View full text |Cite
|
Sign up to set email alerts
|

Offline Dictionary Attack on Password Authentication Schemes Using Smart Cards

Abstract: Abstract. The design of secure and efficient smart-card-based password authentication schemes remains a challenging problem today despite two decades of intensive research in the security community, and the current crux lies in how to achieve truly two-factor security even if the smart cards can be tampered. In this paper, we analyze two recent proposals, namely, Hsieh-Leu's scheme and Wang's PSCAV scheme. We show that, under their non-tamper-resistance assumption of the smart cards, both schemes are still pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
41
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 50 publications
(98 reference statements)
0
41
0
Order By: Relevance
“…Wang, Ma, P. Wang, & Chen, 2012;D. Wang, Ma, & P. Wang, 2012b;D. Wang & P. Wang, 2013;Y, Wang, 2012)also presented the confidence of two authentication protocols of Leu and Hsieh (Hsieh & Leu, 2012) and found that their scheme is defenseless to the offline dictionary.…”
Section: Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…Wang, Ma, P. Wang, & Chen, 2012;D. Wang, Ma, & P. Wang, 2012b;D. Wang & P. Wang, 2013;Y, Wang, 2012)also presented the confidence of two authentication protocols of Leu and Hsieh (Hsieh & Leu, 2012) and found that their scheme is defenseless to the offline dictionary.…”
Section: Related Workmentioning
confidence: 99%
“…Wang, Ma, P. Wang, & Chen, 2012;D. Wang, Ma, & P. Wang, 2012b;D. Wang & P. Wang, 2013;Y, Wang, 2012) present a remarkable learning to examine the trust among smart cards and terminal; that is, whenever an attacker gets a lost smart card, the chance of user's information is being compromised at any stage and at level.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations